IMPROVING BASKETBALL DRIBBLING ABILITY THROUGH 3 ON 3 GAME MODIFICATION - Lau, Devid Tony; Prayoga, Aba Sandi; Darumoyo, Kuncoro (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This study aims to investigate whether the use of 3-on-3 games can improve dribbling skills in basketball. The main objective is to enhance basketball dribbling techniques through the modification of 3-on-3 games in the 7th grade of SMP Negeri 3 Paron. The research method employed in this study is Classroom Action Research. The total number of students in class VIIA is 25, consisting of 14 male students and 11 female students. Findings from the research on the improvement of basketball dribbling skills through the modification of 3-on-3 games indicate that in Cycle I, 14 students successfully completed the task, which is 56%. On the other hand, there were 11 students or 44% who were unable to complete the task. In Cycle II, the test results showed that 21 students or 84% met the completion criteria, while 4 students or 16% did not meet the task requirements. This study provides evidence that through the modification of 3-on-3 games, basketball dribbling skills among students at SMPN 3 Paron can be enhanced. This is evident from the observed improvement from Cycle I to Cycle II.